METAGABRO DEL ARIARI, PLUTONISMO MORB, CORDILLERA ORIENTAL DE COLOMBIA (2014)
Petrographic and geochemical characteristics from Ariari Metagabbro are shown in this paper. The Metagabbro outcrops at La Crystalline creek located eastwards from of El Dorado town, department of Meta in the Eastern Cordillera. This body develops low-grade metamorphism in the green schist facies, but not obliterated the original texture of the rock. The chemical composition of Ariari metagabbro indicates a tholeiitic affnity (gabbros; SiO2= 47.69 - 46.93 wt%, FeO + MgO = 18.42 -19.13 wt% and K2O + Na2O = 4.16-10.42wt %) Nb/Y ratios = 0.13-0.17 with REE patterns characterized by slightly impoverished LREE and less fractionated patterns and relatively fat HREE. The trace element composition shows fractionated LILE patterns, with Cs, Ba and Rb enrichments and a slight negative Pb anomaly. These features suggest that the Ariari Metagabbro was originated in a MORB setting.